2008
DOI: 10.1105/tpc.108.059568
|View full text |Cite
|
Sign up to set email alerts
|

Type B Phosphatidylinositol-4-Phosphate 5-Kinases MediateArabidopsisandNicotiana tabacumPollen Tube Growth by Regulating Apical Pectin Secretion

Abstract: Phosphatidylinositol-4,5-bisphosphate [PtdIns(4,5)P 2 ] occurs in the apical plasma membrane of growing pollen tubes. Because enzymes responsible for PtdIns(4,5)P 2 production at that location are uncharacterized, functions of PtdIns(4,5)P 2 in pollen tube tip growth are unresolved. Two candidate genes encoding pollen-expressed Arabidopsis thaliana phosphatidylinositol-4-phosphate 5-kinases (PI4P 5-kinases) of Arabidopsis subfamily B were identified (PIP5K4 and PIP5K5), and their recombinant proteins were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
264
5
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(296 citation statements)
references
References 100 publications
(132 reference statements)
25
264
5
2
Order By: Relevance
“…While the chemical basis for PI fluorescence in the pollen tube apical wall has not been established, we suspect that its positive charge allows the dye to interact with negative charges on pectin (i.e., carboxyl residues) in a manner similar to several other pectin dyes, such as ruthenium red (Ischebeck et al, 2008;Szumlanski and Nielsen, 2009), coriphosphine O (Weis et al, 1988), and cobalt and nickel (Varner and Taylor, 1989;Jauneau et al, 1997). That PI fluorescence and DIC thickness measurements provide nearly identical results strongly supports the conclusion that these two independent assays respond to the same feature.…”
Section: Wall Thickness and Pi Fluorescence Are Valid Estimates Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…While the chemical basis for PI fluorescence in the pollen tube apical wall has not been established, we suspect that its positive charge allows the dye to interact with negative charges on pectin (i.e., carboxyl residues) in a manner similar to several other pectin dyes, such as ruthenium red (Ischebeck et al, 2008;Szumlanski and Nielsen, 2009), coriphosphine O (Weis et al, 1988), and cobalt and nickel (Varner and Taylor, 1989;Jauneau et al, 1997). That PI fluorescence and DIC thickness measurements provide nearly identical results strongly supports the conclusion that these two independent assays respond to the same feature.…”
Section: Wall Thickness and Pi Fluorescence Are Valid Estimates Of Thmentioning
confidence: 99%
“…Although the basis for staining is not known, PI carries positive charges and may interact with the negative charges that are present on the pectins, especially the carboxyl residues. The basis for PI staining may therefore be similar to other reagents better known for their ability to react with pectin, such as ruthenium red (Ischebeck et al, 2008;Szumlanski and Nielsen, 2009), coriphosphine O (Weis et al, 1988), and nickel or cobalt (Varner and Taylor, 1989;Jauneau et al, 1997), which also carry positive charges. We have applied PI to growing pollen tubes of lily and tobacco.…”
Section: Pi Staining Provides a Sensitive Assay For Wall Materials Inmentioning
confidence: 99%
“…Besides 4 homologs of yeast PIP5K, 11 PIPK isoforms can be divided into two subfamilies (A and B) according to their domain organization [14]. The catalytic activities of using PtdIns4P as the preferred substrate to generate PtdIns(4,5)P 2 have all been characterized [15][16][17][18]. Studies have revealed the physiological functions of some PIP5Ks, including PIP5K1 in abscisic acid signaling [19]; PIP5K3 in root hair formation and growth [16,20]; PIP5K4 in stomata opening [21]; and PIP5K4-6 in pollen tube growth [17,22].…”
Section: Introductionmentioning
confidence: 99%
“…10 It is clear that it is not the N-terminal MORN domain responsible for these differences in phenotypes observed between type A and B subfamilies, since overexpression of mutated isoforms lacking the MORN domain from AtPIP5K3 or AtPIP5K5 resulted in the same phenotypes as that of full-length proteins. 9,11 In P. patens, both PIPKs are expressed in protoplasts, protonema and gametophores. 7 The disruption of both genes by gene targeting showed that both enzymes are involved in tip growth.…”
Section: What Drives Pipks To the Plasma Membrane?mentioning
confidence: 99%
“…It has been shown that PtdIns4P is the preferred substrate in vitro for the synthesis of PtdIns(4,5)P 2 by all AtPIPKs; [8][9][10][11][12] this is also the case for PpPIPK1, but not for PpPIPK2, which in vitro prefers PI to produce PtdIns3P. 7 However, we have shown that in vivo both PpPIPK1 and PpPIPK2 catalyze the synthesis of PtdIns(4,5)P 2 , since the knockout lipid profile showed a reduction only in PtdIns(4,5)P 2 in both pipk1 and pipk2 mutants.…”
Section: Activation Modes Of Plant Pipksmentioning
confidence: 99%